Egy kistérség sikerének titka – avagy tettek és tervek a Nyugati-Kapu Térségfejlesztési Társulás „házatáján” - Szörényiné Kukorelli, Irén (Tér és Társadalom, 1997)
The study aimed at reviewing the main factors of the success of the micro-region of "Nyugati-Kapu Regional Development Association". We focused on human, geographical and environmental conditions of development. Geographical situation determined by the vicinity of the national border and transportation routes of intemational importance are a major potential for economic development. It must be exploited by the local leaders and entrepreneurs through initiation of international co-operation and extension of economic relations. In this way, favourable geographical conditions must be combined by human factors to achieve social progress in the region. A concept for regional development that rests on the analysis of endogenous resources and geographical potential (summarised in the SWOT analysis) shall give a further stimulus for the collaboration and success of mutual programs. The study also presents the priorities and programs that based on the concept and should be realised in the region.